Various Subtypes of EGFR Mutations in Patients With NSCLC Define Genetic, Immunologic Diversity and Possess Different Prognostic Biomarkers - Lei, Youming; Wang, Kun; Liu, Yinqiang; Wang, Xuming; Xiang, Xudong; Ning, Xiangu; Ding, Wanbao; Duan, Jin; Li, Dingbiao; Zhao, Wei; Li, Yi; Zhang, Fujun; et al. (Frontiers in Immunology, 2022)
Based on data analysis of 9659 Chinese primary NSCLC patients, we calculated the exact proportion of EGFR subtypes in NSCLC and evaluated the TMB level, PD-L1 expression level and tumor immune microenvironment among different EGFR mutation subtypes. Postoperative follow-up data for 98 patients were collected and analyzed. The results showed that several uncommon EGFR subtypes have a higher proportion of TMB-high or strong positive PD-L1 expression than the total EGFR mutation group. In addition, different subtypes have different characteristics related to the immune microenvironment, such as G719 mutations being associated with more CD8+ T cell infiltration into tumors; except for EGFR 19del, CD8+ T cell infiltration into tumors of other EGFR mutation subtypes were similar to that of wildtype EGFR. Moreover, follow-up results revealed that components of the immune microenvironment have prognostic value for NSCLC patients, with different prognostic biomarkers for NSCLC patients with and without EGFR mutations. These results suggest that patients with different EGFR mutations need to be treated differently. The prognosis of NSCLC patients may be assessed through TIME components, and ICI treatment may be considered for those with some uncommon EGFR mutation subtypes.